Lifting the Mask: Performance and Real Presence in Dante - Cornish, Alison (Quaderni d'Italianistica)

(untitled) (Iter Press, 2024)
With our new sensibility to faces hidden by and emerging from behind masks, as well as to the dangers associated with seeing unmasked faces, this essay gives consideration to these themes in the Divine Comedy in relation to the question of performance. The blessed souls appearing to Dante descend to the physical spheres in a “command performance” with vague outlines of faces ceding to even less discernible brightnesses. The vision of those same souls as faces assembled in the Empyrean, where they in fact reside, is also staged, as they are shown as they will appear only at the end of time. Yet this performance is described as people removing their masks. The final vision of God seems to be a specular glimpse of one’s own face (nostra effige) in the Incarnation. This essay juxtaposes contemporary ideas of performativity developed out of speech act theory with medieval practical theology, such as the performance of the psalms and the liturgy and iconography of the Eucharist, in which performance effects what is often referred to as “real presence”. In particular, the imago pietatis, or Man of Sorrows, unwittingly echoed in the stance of the proud atheist, Farinata, in Hell, connects real presence to knowledge of the present, both of which are invisible to the damned. The episode of Ugolino, meanwhile, connects seeing faces with eating, glossed by the extreme legibility on the faces of the starving on the terrace of gluttons in Purgatory. By the end of the poem, true knowledge is expressed not as propositional dogma or science of facts but as an ineffable participatory experience: seeing a face, feeding at the breast, and performing or enacting a relationship of love.